Agora: A Dependable High-Performance Coordination Service for Multi-Cores - Schiekofer, Rainer; Behl, Johannes; Distler, Tobias (Proceedings of the 47th International Conference on Dependable Systems and Networks (DSN '17), 2017)
UnivIS-Import:2017-03-24:Pub.2017.tech.IMMD.IMMD4.agoraa
Keywords: REFIT; EDC

CheapBFT: Resource-efficient Byzantine Fault Tolerance - Kapitza, Rüdiger; Behl, Johannes; Cachin, Christian; Distler, Tobias; Kuhnle, Simon; Mohammadi, Seyed Vahid; Schröder-Preikschat, Wolfgang; Stengel, Klaus (Proceedings of the EuroSys 2012 Conference (EuroSys '12), 2012)
One of the main reasons why Byzantine fault-tolerant (BFT) systems are not widely used lies in their high resource consumption: 3f + 1 replicas are necessary to tolerate only f faults. Recent works have been able to reduce the minimum number of replicas to 2f + 1 by relying on a trusted subsystem that prevents a replica from making conflicting statements to other replicas without being detected. Nevertheless, having been designed with the focus on fault handling, these systems still employ a majority of replicas during normal-case operation for seemingly redundant work. Furthermore, the trusted subsystems available trade off performance for security; that is, they either achieve high throughput or they come with a small trusted computing base. This paper presents CheapBFT, a BFT system that, for the first time, tolerates that all but one of the replicas active in normal-case operation become faulty. CheapBFT runs a composite agreement protocol and exploits passive replication to save resources; in the absence of faults, it requires that only f + 1 replicas actively agree on client requests and execute them. In case of suspected faulty behavior, CheapBFT triggers a transition protocol that activates f extra passive replicas and brings all non-faulty replicas into a consistent state again. This approach, for example, allows the system to safely switch to another, more resilient agreement protocol. CheapBFT relies on an FPGA-based trusted subsystem for the authentication of protocol messages that provides high performance and comprises a small trusted computing base. © 2012 AC
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD4.cheapb
Keywords: TCLOUDS; REFIT

Consensus-Oriented Parallelization: How to Earn Your First Million - Behl, Johannes; Distler, Tobias; Kapitza, Rüdiger (Proceedings of the 16th Middleware Conference (Middleware '15), 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.IMMD.IMMD4.consen
Keywords: REFIT

DQMP: A Decentralized Protocol to Enforce Global Quotas in Cloud Environments - Behl, Johannes; Distler, Tobias; Kapitza, Rüdiger (Proceedings of the 14th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS '12), 2012)
Platform-as-a-Service (PaaS) clouds free companies of building infrastructures dimensioned for peak service demand and allow them to only pay for the resources they actually use. Being a PaaS cloud customer, on the one hand, offers a company the opportunity to provide applications in a dynamically scalable way. On the other hand, this scalability may lead to financial loss due to costly use of vast amounts of resources caused by program errors, attacks, or careless use. To limit the effects of involuntary resource usage, we present DQMP, a decentralized, fault-tolerant, and scalable quota-enforcement protocol. It allows customers to buy a fixed amount of resources (e.g., CPU cycles) that can be used flexibly within the cloud. DQMP utilizes the concept of diffusion to equally balance unused resource quotas over all processes running applications of the same customer. This enables the enforcement of upper bounds while being highly adaptive to all kinds of resource-demand changes. Our evaluation shows that our protocol outperforms a lease-based centralized implementation in a setting with 1,000 processes. © 2012 Springer-Verlag.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD4.dqmpad
Keywords: TCLOUDS

Hybrids on Steroids: SGX-based High Performance BFT - Behl, Johannes; Distler, Tobias; Kapitza, Rüdiger (Proceedings of the 12th European Conference on Computer Systems (EuroSys '17), 2017)
UnivIS-Import:2017-03-24:Pub.2017.tech.IMMD.IMMD4.hybrid
Keywords: REFIT

Providing Fault-tolerant Execution of Web-service-based Workflows within Clouds - Behl, Johannes; Distler, Tobias; Heisig, Florian; Kapitza, Rüdiger; Schunter, Matthias (Proceedings of the 2nd International Workshop on Cloud Computing Platforms (CloudCP '12), 2012)
With a variety of services rapidly evolving at all architectural levels of cloud computing, there is an increasing demand for a standardized way to coordinate their interactions. Business process management, that is, more general, the management of Web-service-based workflows, could satisfy this demand and, indeed, first corresponding offerings have gained instant popularity. While from a functional perspective, these Platform-as-a-Service (PaaS) solutions are already quite mature, their support for fault tolerance is still very limited, making them inapplicable for critical tasks. Concerning the deficiencies of currently existing systems, this paper presents a practical solution for executing critical Web-service-based workflows, particularly within clouds, in a fault-tolerant, highly available and highly configurable manner. We achieve this by actively replicating workflows as well as Web services in a combined architecture, reusing existing standard systems and coordination services. By providing an automated transformation tool, replication is realized transparently to existing systems and workflows. Measurements show that our proposed architecture achieves lower response times than existing systems and that the integration of a coordination service imposes only moderate costs, while simplifying the implementation and leading to a dynamically adaptable solution. © 2012 ACM.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD4.provid
Keywords: TCLOUDS

Scalable BFT for Multi-Cores: Actor-based Decomposition and Consensus-oriented Parallelization - Behl, Johannes; Distler, Tobias; Kapitza, Rüdiger (Proceedings of the 10th Workshop on Hot Topics in System Dependability (HotDep '14), 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD4.scalab
Keywords: REFIT